1995
DOI: 10.1016/0013-4694(95)00055-4
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory event-related potentials in normal human subjects: effects of age and gender

Abstract: Olfactory event-related potentials in normal human subjects: effects of age and gender AbstractBehavioral and electrophysiological testing of olfactory function was performed in 33 normal human male and female subjects, 18-83 years of age. Acuity for odor identification and odor detection was verified by standard psychophysical tests. For evoked potential testing, a constant flow olfactometer provided odorant stimuli (amyl acetate) or air control stimuli that were presented to the right nostril by a nasal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(27 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Additionally, women of different ages (18–83 years old) have larger olfactory evoked potential amplitudes to amyl acetate than men [23], and higher cerebral blood flow and cerebral metabolic rate of glucose utilization (18–33 years old) [30]. This may mean that female OBs transfer a greater amount of excitatory olfactory information to the subsequent cortical stages than is the case for males, what would agree with women’s richer neuronal machinery in their olfactory bulbs, as shown in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, women of different ages (18–83 years old) have larger olfactory evoked potential amplitudes to amyl acetate than men [23], and higher cerebral blood flow and cerebral metabolic rate of glucose utilization (18–33 years old) [30]. This may mean that female OBs transfer a greater amount of excitatory olfactory information to the subsequent cortical stages than is the case for males, what would agree with women’s richer neuronal machinery in their olfactory bulbs, as shown in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Some attempts have been made, and evidence has been produced by electrophysiological recording of event-related potentials [23][25], confirming the superiority of women in odor detection and emotional valence. Functional neuroimaging, on the other hand, has proved controversial so far, with negative [26] and positive [27] evidence for olfactory dimorphism, the latter favoring superior olfactory abilities by women.…”
Section: Introductionmentioning
confidence: 91%
“…During stimulation, the airflow (8 l/min), temperature (36°C) and humidity (80% relative humidity) remain strictly unchanged, thus avoiding any concomitant stimulation of mechanical or heat sensitive trigeminal receptors. Trigeminal stimuli were generated by gaseous CO 2 (55% v/v) used to activate trigeminal afferents, and olfactory stimuli were generated by 2-Phenylethanol (50% v/v) used to activate olfactory afferents [5], [59]. The stimuli were delivered through a Teflon™ tube placed in the right nostril, just behind the nasal valve, pointing towards the olfactory cleft.…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations focused on gender differences (for review see [8]) and reported that women outperform men in olfactory tasks [9,10]. Most of the studies claimed a female superiority, attributed to hormonal factors, which was thought to be the result of better verbal abilities regarding olfactory testing and ratings [11]. Regardless of the verbal components and olfactory test construction, basic chemosensory processing was shown to be different across sexes in direct recordings using olfactory event related potentials [12] and at a neuronal level [13].…”
Section: Introductionmentioning
confidence: 99%